2018
DOI: 10.1007/s00253-018-8921-9
|View full text |Cite
|
Sign up to set email alerts
|

A 12-residue epitope displayed on phage T7 reacts strongly with antibodies against foot-and-mouth disease virus

Abstract: Foot-and-mouth disease (FMD) is a major threat to the livestock industry worldwide. Despite constant surveillance and effective vaccination, the perpetual mutations of the foot-and-mouth disease virus (FMDV) pose a huge challenge to FMD diagnosis. The immunodominant region of the FMDV VP1 protein (residues 131-170) displayed on phage T7 has been used to detect anti-FMDV in bovine sera. In the present study, the functional epitope was further delineated using amino acid sequence alignment, homology modelling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…With detection sensitivity of 0.999 and specificity of 0.959 [23] Mycobacterium tuberculosis infection With detection sensitivity of 1 and specificity of 1 [24] Foot-and-mouthdisease Identifying functional epitope VP1159-170 [25] Alzheimer'sdisease (AD) Identifying a panel of AD autoantibodies [26] Autoimmuneretinopathy By immunoprecipitation sequencing (PhIP-Seq) [27] Lung tumor Constructing lung tumor protein chip based on T7 phages [28] Melanoma By T7 phage display antigen microarrays [29] Detection of E. coli In water Detection of less than 10 CFU mL −1 E. coli in 3 h [30] In drinking water Detection of 1 × 10 4 CFU mL −1 within 2.5 h [31] In beverages Detecting alkaline phosphatase [32] In food and water Detecting alkaline phosphatase maltose-binding protein [33] In food matrices Detecting the overexpressed enzymes [34] E. coli Detecting the overexpressed luciferase [35] E. coli For phages and for antibiotic resistance testing [36] Detection of pathogens Viable bacterial pathogens By T7 phages carried tobacco etch virus (TEV) protease [37] Table 2. Review of targeted therapy based on T7 phage.…”
Section: Serological Biomarkers Cystic Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…With detection sensitivity of 0.999 and specificity of 0.959 [23] Mycobacterium tuberculosis infection With detection sensitivity of 1 and specificity of 1 [24] Foot-and-mouthdisease Identifying functional epitope VP1159-170 [25] Alzheimer'sdisease (AD) Identifying a panel of AD autoantibodies [26] Autoimmuneretinopathy By immunoprecipitation sequencing (PhIP-Seq) [27] Lung tumor Constructing lung tumor protein chip based on T7 phages [28] Melanoma By T7 phage display antigen microarrays [29] Detection of E. coli In water Detection of less than 10 CFU mL −1 E. coli in 3 h [30] In drinking water Detection of 1 × 10 4 CFU mL −1 within 2.5 h [31] In beverages Detecting alkaline phosphatase [32] In food and water Detecting alkaline phosphatase maltose-binding protein [33] In food matrices Detecting the overexpressed enzymes [34] E. coli Detecting the overexpressed luciferase [35] E. coli For phages and for antibiotic resistance testing [36] Detection of pathogens Viable bacterial pathogens By T7 phages carried tobacco etch virus (TEV) protease [37] Table 2. Review of targeted therapy based on T7 phage.…”
Section: Serological Biomarkers Cystic Fibrosismentioning
confidence: 99%
“…[118,119] By introducing the T7 phage display system into the detection of serological biomarkers, this new type of diagnostics can be more accurate, convenient, and efficient. [23][24][25][26][27][28][29][30][31][32][33] For example, Talwar et al isolated mRNA from leukocytes and bronchoalveolar lavage (BAL) cells of patients with nodule disease, and then extracted cDNA library of T7 phages. [23] They constructed a microarray platform, and screened serum from lung cancer patients, cystic fibrosis subjects, and healthy controls.…”
Section: Detection Of Serological Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Wong et al (52) genetically fused the capsid protein of T7 bacteriophage with the VP1 of FMDV and demonstrated that the recombinant protein, when served as the coating antigen in an indirect ELISA, could react with the vaccinated and positive infected bovine sera, suggesting its potential application in FMD diagnosis. Wong et al (53) further delineated the VP1 sequence of FMDV to 12-amino-acid residues using amino acid sequence alignment, homology modeling, and phage display, in which the chimeric phage T7 displaying VP1 159−170 epitope was demonstrated to have an improved sensitivity of 100% in a phage-based ELISA. Recently, a multiple-epitope protein (B4) comprising the G-H loops of VP1 from three topotypes of FMDV serotype O was developed as a potential vaccine candidate (54,103).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…Phage particles can also induce a strong cellular immune response [15]. Related studies have found that the peptides displayed by T7 phage bind closely to FMD serum [24]. To develop an effective FMD vaccine, we here conducted a meta-analysis and used a phage to display the FMD VP1 protein.…”
Section: Introductionmentioning
confidence: 99%